Genotyping of Leptospira spp. in wild rats leads to first time detection of L. kirshneri serovar Mozdok in Serbia - Gajdov, Vladimir; Jokic, Goran; Savic, Sara; Zekic, Marina; Blazic, Tanja; Rajkovic, Milica; Petrovic, Tamas (Frontiers in Microbiology, 2024)
In our recent study, we explored the presence and performed molecular typing of the Leptospira species, the bacteria responsible for leptospirosis, in wild rats in Serbia. This was the first time such a study was conducted in the region. Leptospirosis is a serious disease that affects both animals and humans, often transmitted through contact with water contaminated by infected animals. Our focus was on understanding which types of Leptospira were present in these animals. Excitingly, we discovered a particular strain of Leptospira, known as L. kirshneri serovar Mozdok, for the first time in Serbia. This finding is significant because it sheds light on the presence and spread of different Leptospira serovars in Serbia. It also raises awareness about the potential health risks associated with this serovar, which was previously unknown in the area. Our work fits into a broader context of disease surveillance and public health. By identifying the types of Leptospira present in a specific region, we can better understand the risks to public health and take steps to prevent and control the spread of leptospirosis. This discovery is not just important for scientists studying infectious diseases; it has real implications for public health officials, veterinarians, and anyone concerned with preventing and treating leptospirosis. Our findings highlight the need for ongoing monitoring of Leptospira in wildlife and synanthropic faunawildlife, to protect both animal and human health.